Distribution and internal correlations of corneal astigmatism in cataract patients - Jiang, Yuanfeng (Sci Rep, 2021)
The aim of the study is to explore the distribution patterns and internal correlations of the morphological parameters of the cornea in patients with age-related cataract. The Pentacam HR was used to measure anterior corneal astigmatism (ACA), posterior corneal astigmatism (PCA), total corneal astigmatism (TCA) and keratometric corneal astigmatism (KCA). With age, the proportion of with-the-rule (WTR) ACA decreased from 65.31% to 23.63%, while the against-the-rule (ATR) ACA increased from 26.53% to 56.20%. PCA exceeded 0.50 D in 9.14% of eyes, while 76.35% of them were ATR. The magnitude of ACA was positively correlated with PCA in the whole sample, with a more significant correlation in WTR eyes (s(r) = 0.349, P < 0.001). The vector summation effect of PCA to ACA changed from compensation to augmentation with aging. In 57.53% of WTR eyes, KCA was overestimated by an average of 0.21 ± 0.17 D, while it was underestimated by 0.38 ± 0.27 D in 87.62% of ATR eyes. In conclusion, among age-related cataract patients, ACA and TCA gradually shifted from WTR to ATR with aging, while most PCA remained as ATR. Ignoring the age-related changes and real PCA might cause overestimation of WTR astigmatism and underestimation of ATR astigmatism.